Primary dural lymphoma: Complete remission after treatment with radiation therapy - Jones, Jeremy; Gupta, Arjun; Naina, Harris (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Central nervous system (CNS) involvement in sarcoidosis is rare and typically occurs in 5-10% of patients. Neurological symptoms in a patient with known sarcoidosis can be attributed to neurosarcoidosis without thorough evaluation. Primary Dural Lymphoma (PDL) is an extremely rare form of non-Hodgkin lymphoma. Although PDL is technically a subtype of primary CNS lymphoma, the two entities vary markedly in their histological grade, clinical course, prognosis and treatment. The most common dural- based lesion found on CNS imaging is meningioma. It shares many imaging, clinical and epidemiologic features of PDL which often leads to misdiagnosis of PDL as meningioma. We present a case where a PDL was diagnosed after CNS symptoms failed to resolve after steroid therapy for presumed neurosarcoidosis.